2017
DOI: 10.3389/fpls.2017.00420
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity under Soil Compaction in Wheat: Root Number as a Promising Trait for Early Plant Vigor

Abstract: Soil compaction of arable land, caused by heavy machinery constitutes a major threat to agricultural soils in industrialized countries. The degradation of soil structure due to compaction leads to decreased (macro-) porosity resulting in increased mechanical impedance, which adversely affects root growth and crop productivity. New crop cultivars, with root systems that are adapted to conditions of increased soil strength, are needed to overcome the limiting effects of soil compaction on plant growth. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 55 publications
2
25
0
2
Order By: Relevance
“…The relation of root system architecture to crop performance in wheat is partially established, but many gaps in knowledge remain. A recent study found a positive correlation of root number with enhanced growth in compacted soil (Colombi and Walter, 2017). QTLs for root angle and number overlapped with QTLs for yield in a wheat mapping population (Canè et al , 2014), and again in another study (Maccaferri et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The relation of root system architecture to crop performance in wheat is partially established, but many gaps in knowledge remain. A recent study found a positive correlation of root number with enhanced growth in compacted soil (Colombi and Walter, 2017). QTLs for root angle and number overlapped with QTLs for yield in a wheat mapping population (Canè et al , 2014), and again in another study (Maccaferri et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, incorporating selection for root traits directly in a breeding program has been met with many challenges, foremost the difficulty of phenotyping large numbers of genotypes in a cost-and time-efficient manner (Mace et al, 2012). Several wheat studies have evaluated roots using different phenotyping methods including rhizotrons (Nagel et al, 2012;Lobet and Draye, 2013;Clarke et al, 2017), soil coring (Trachsel et al, 2011;Wasson et al, 2012;Wasson et al, 2014), lysimeters (Ehdaie et al, 2014;Elazab et al, 2016), hydroponics (Liu et al, 2015), paper roll culture and Petri dishes for seedling (Tomar et al, 2016), rhizoboxes (Fang et al, 2017, and X-ray-computed tomography (Gregory et al, 2003;Mairhofer et al, 2013;Colombi and Walter, 2017;Flavel et al, 2017). However, most of these techniques are either expensive or not precise enough and reproducible.…”
Section: Root System Architecture and Its Association With Yield Undementioning
confidence: 99%
“…(Bushamuka and Zobel, 1998), pea (Pisum sativum L.; Clark et al, 1999), rice (Oryza sativa L.; Clark et al, 2000), and wheat (Colombi and Walter, 2017). (Bushamuka and Zobel, 1998), pea (Pisum sativum L.; Clark et al, 1999), rice (Oryza sativa L.; Clark et al, 2000), and wheat (Colombi and Walter, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Merr.] (Bushamuka and Zobel, 1998), pea (Pisum sativum L.; Clark et al, 1999), rice (Oryza sativa L.; Clark et al, 2000), and wheat (Colombi and Walter, 2017).…”
Section: Resultsmentioning
confidence: 99%